2014
DOI: 10.4314/sajas.v44i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cage tier and age on performance, egg quality and stress parameters of laying hens

Abstract: This study was conducted to investigate the effects of cage tier and age on performance characteristics of layer hybrids, egg quality and some stress parameters. Ninety laying hens (hybrid ATAK-S) of similar bodyweights were used in the experiment. They were housed in three-tier conventional battery cages (bottom, middle and top) with 600 cm 2 /per bird. The experiment was conducted on hens from the age of 18 weeks to 42 weeks. Layers at the age of 18 weeks were randomly allocated to conventional three-tier ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
4
21
1
Order By: Relevance
“…In the present study, there was no difference for egg shape index of both light source types (P > 0.05). There were studies reporting that the cage tier did not affect the egg shape index [2,18,24,33,40]. However, in the present study, cage tier affected egg shape index (P < 0.05).…”
Section: Egg Qualitycontrasting
confidence: 77%
See 3 more Smart Citations
“…In the present study, there was no difference for egg shape index of both light source types (P > 0.05). There were studies reporting that the cage tier did not affect the egg shape index [2,18,24,33,40]. However, in the present study, cage tier affected egg shape index (P < 0.05).…”
Section: Egg Qualitycontrasting
confidence: 77%
“…Thus, in the present study, the Haugh unit value was similar in both light type groups (P > 0.05). Karaman et al [33], Yıldız et al [44], and Şekeroğlu et al [24] reported that the Haugh unit value was also similar between the cage tiers of conventional battery cage system. In accordance with their results, we have found that the effect of cage tiers on the Haugh unit value was found to be similar (P > 0.05).…”
Section: Interactionsmentioning
confidence: 90%
See 2 more Smart Citations
“…The effect of lighting type and cage-tier interaction on TI duration and induction number was not significant at 45 weeks of age (P > 0.05). However, Şekeroğlu et al [33] T er reported that the shortest TI duration was found in low level cage tiers at 30 weeks of age. They also reported that there was no difference between the cage tiers regarding TI duration of layers at 45 weeks of age; however, TI duration was numerically lower at bottom cage tiers as aging progressed.…”
Section: Some Welfare Behavior Traitsmentioning
confidence: 92%